The Importance of Linguocultural Analysis In The Gothic Style - Makhmudov, Kudratbek (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Readers worldwide have been captured by the Gothic style in literature, which is characterized by themes of the supernatural, darkness, and mystery, and has resonated across various cultural contexts. Its components mirror universal human concerns through a distinctively dark lens, revealing deep-rooted cultural fears, moral dilemmas, and social anxieties. The underlying meanings of Gothic works are crucially revealed through linguistic analysis, which investigates language within its cultural context. Linguocultural perspectives offer more comprehensive interpretations of Gothic themes by examining language choices, cultural references, and symbolism, thereby revealing the ways in which they differ across cultures and time periods. In this review, we investigate the significance and cultural profundity of the Gothic style by examining the role of linguocultural analysis.